Designing Flow-Based Chatbot as Student Information Service Center - Amalia Anjani Arifiyanti; Ivan Faiz Daniar; Reisa Permatasari; Abdul Rezha Efrat Najaf (Future Science, 2023)
Universities strive to enhance public services to continually elevate user satisfaction. One critical aspect of public service is the accessibility and transparency of information, particularly in ensuring that students can easily access relevant information, contributing to heightened satisfaction with the university. However, while fostering openness and accessibility, adequate resources are essential to manage the surge in information requests from students. Chatbots emerge as a viable solution for disseminating information on academic activities, providing easy accessibility unhindered by temporal or spatial constraints at UPN